Surgical treatment of squamous cell carcinoma of tongue with carbon dioxide laser radiation (CO2) - Niccoli-Filho, Walter [UNESP]; Murilo-Santos, Lucio [UNESP]; Morosolli, Aline R. C.; Moura Cardoso, Gerusa de Oliveira [UNESP]; dos Santos Canellas, Joao Vitor [UNESP] (American Institute of Physics (AIP), 2012)
In this clinical study, we proposed to observe the efficacy of the treatment of squamous cell carcinoma of the tongue (SCCT) by carbon dioxide (CO2) laser surgery. Twelve patients with SCCT were treated with excisional surgery using the CO2 laser with a spot size of 0.8 mm, 10 W, power density of 2.5 W/cm(2) in continuous mode, and under constant vacuum removal of the plume. The post surgical clinical evaluations were done every day until the sutures were removed and then every 7 days up to 1 month postoperatively. Subjects were re-examined quarterly until the fifth year post surgery. After 5 yr of follow-up for all subjects, there was no recurrence of the SCCT at the involved sites. The functional and aesthetic results observed were excellent. It is concluded that CO2 laser ablation of SCCT is an extremely useful surgical technique that can provide a clean field and is capable of providing surgical results consistent with accepted principles of oncological surgery. (C) 2012 Laser Institute of America.
Keywords: Squamous cell carcinoma; oral cancer; tongue; carbon dioxide laser radiation